Strategi Komunikasi Deteksi Dini Kanker Serviks di Kota Bandung - Rina Mariana (MediaTor (Jurnal Komunikasi), 2019)
A good and planned communication strategy is not only a tool to provide knowledge and education, but moreover it is full of persuasive content that can encourage the target audience to act in accordance with predetermined communication objectives. The purpose of this study was to develop a communication strategy as an effort to support the health program of early detection of cervical cancer in the form of IVA or Pap smear examinations by referring to the description of the initial attitude of the study respondents. The method used in this research is descriptive quantitative. The research was conducted in Bandung in April 2018 involving 50 respondents. Data analysis was performed statistically which included data tabulation, descriptive statistical analysis, and interpretation thereof. The results showed that the level of knowledge about early detection of cervical cancer is still low in line with the very low behavior of respondents in conducting early cervical cancer examination so that it requires a persuasive communication strategy so that public awareness and concern for this health program can increase